Elastocapillary cleaning of twisted bilayer graphene interfaces - Yuan Hou (Nature Portfolio, 2021)
Here, the authors investigate the long-range interaction and coalescence mechanism of water and ethanol nanopockets encapsulated in twisted bilayer graphene, showing the complete recovery of moiré patterns after the motion of the contaminants.